Ultrasound-guided stellate ganglion blockade – patient positioning is everything: a case report demonstrating the efficacy of a modified out-of-plane approach - Mo, Ke; Qian, Liang; Tian, Jingling; Liao, Junling; Tan, Fang; Kong, Weirong; Yu, Xianjun; Chi, Xinjin (Frontiers in Neuroscience, 2024)
Background: Insomnia has become increasingly prevalent in modern society and is notoriously difficult to treat. Many patients exhibit a poor response to pharmacological interventions. Stellate ganglion block (SGB) has emerged as an effective method for managing insomnia; however, its efficacy may be compromised in some patients, primarily due to a variant vertebral artery anatomy. Case Presentation: This case report describes a patient with severe insomnia accompanied by anxiety. Through cervical ultrasound scanning, we identified richly branched cervical arteries at the C6–C7 segment of the vertebral artery, along with anatomical variations, which could pose a heightened risk for the traditional SGB procedure. Therefore, after carefully adjusting the patient's positioning, we proceeded with ultrasound-guided SGB using a lateral paravein out-of-plane approach. Clinical signs of successful insomnia symptoms alleviation were consistently observed after each block utilizing this alternative technique multiple times in a single patient. Conclusions: Our report reveals a new lateral paravein out-of-plane approach for ultrasound-guided SGB to treat insomnia, which might be considered an alternative method. More studies should be carried out to confirm the efficacy of this new approach.